Peran Jurnalisme Media Sosial dalam Mewujudkan Demokrasi Indonesia di Era Post Truth - Sadryna Evanalia (Badan Pengawas Pemilihan Umum, 2022)
Social Media is one of the public spaces for discussing and participating in politics to realize democracy. However, social media also has a weakness in disseminating hoaxes, misinformation, and exposing the Post Truth phenomenon that threatens the sustainability of democracy in Indonesia. The Normative Media Theory suggests that a media should (1) guarantee freedom of opinion, (2) convey information and know the truth, (3) be independent and reduce the interests of media owners, (4) have a variety of information available to the public, (5) reach out to the public. broadly various audiences, (6) supports a democratic political system, (7) and respects the privacy and human rights in general. This study investigates the role of KompasTV social media in realizing democracy in the post-truth era as a form of social media journalism. The research method used is descriptive qualitative with data collection in the form of observations and interviews. From the results of the research, it was found that KompasTV social media journalism upholds aspects of the Normative Media Theory perspective by prioritizing news value, verification, and fact-checking to ward off and avoid hoaxes, due to important and interesting things for the community. However, as a media that plays in the realm of social media, KompasTV in the pre-election period used SEO (Search Engine Optimization), Trending Topics, and viral issues in its journalistic production to increase views. Meanwhile, during the election period, KompasTV social media put forward the principle of balance.